Pemanfaatan Teknologi Digital dalam Meningkatkan Minat Belajar PPKn Siswa di Sekolah Dasar - Tiara Genisa; Vinanda Asmaul Husna; Adrias Adrias; Salmaini Safitri Syam (Jurnal Bintang Pendidikan Indonesia, 2025)
Digital technology is increasingly being used in education, especially in primary school subjects such as Pancasila and Civic Education (PPKn). However, a significant obstacle that still needs to be overcome is learners' disinterest in civics lessons. The purpose of this study is to find out how learners' desire to learn in elementary school is influenced by the utilization of digital technology in Civics learning. The Systematic Literature Review (SLR) approach is the research methodology used to structure this study by reviewing a maximum of 10 journal articles published between 2023-2025. This method involves searching, discussing, evaluating and interpreting related research that is currently available. Findings from the literature review show that the use of digital technology in the classroom can increase students' enthusiasm for learning. High student attention and active engagement in the learning process serves as proof of this.